PICKPOCKET DISCOURSE COMMUNITY SEEN IN OLIVER TWIST MOVIE - Utami Ratna Swari (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2017)
This study is qualitative study and focus on the sociolinguistics which studying language andsociety of a certain community. The emphasis of this study is discourse community. The discoursecommunity must have all these qualities or it is not a discourse community. Swales definition sets aprofessional tone to the term discourse community, a central community in Oliver Twist , that isPickpocket community. Thus, this study aiming to analyze further about the pickpocket discoursecommunity seen in Oliver Twist movie based on the six characteristics of discourse community definedby Swales.